Exploration of Symbiotic Bacteria with Potential as Degraders of Cypermethrin Insecticide in the Digestive Tract of Onion Caterpillar Spodoptera exigua (Lepidoptera: Noctuidae) in Kediri Regency - Mochammad Syamsul Hadi; Tita Widjayanti; M Henry Fathur Rachman; Achmad Fitriadi Taufiqurrahman; Sholikah Widyanitta Rachmawati (Jurnal Ilmu Lingkungan, 2025)
Onion caterpillar (Spodoptera exigua Hubner) is one of the major pests of onion plants, causing significant damage by consuming the inner parts of the leaves and perforating the leaf tips. In the Badas, Plemahan, and Kepung sub-districts, control of this pest is intensively carried out using the insecticide cypermethrin, which has led to resistance in S. exigua. This resistance is suspected to be influenced by the presence of symbiotic bacteria in the caterpillar's digestive tract that can degrade the active ingredient of the insecticide cypermethrin. This study aims to explore, identify, and determine the potential of symbiotic bacteria in degrading cypermethrin in the digestive tract of S. exigua in Kediri Regency. The research was conducted in three sub-districts in Kediri Regency and at the Plant Toxicology Laboratory, Faculty of Agriculture, Brawijaya University, using a Completely Randomized Design (CRD) method to test the ability of symbiotic bacteria to degrade cypermethrin. The results showed that 26 bacterial strains were successfully isolated from the digestive tract of S. exigua, of which 14 isolates showed the ability to degrade cypermethrin. The two best isolates, B7 and P6, belonging to the genus Erwinia, are suspected to be capable of degrading the insecticide cypermethrin, producing average clear zones of 1.025 cm and 1.2 cm, respectively. Further identification revealed that the isolates consisted of 9 isolates of the genus Pantoea, 4 isolates of the genus Erwinia, and 1 isolate of the genus Clostridium.